Developing a demand planning strategy for joint forecasting and employing analytical tool in an empirical case study - Kiran Basavaraju; Omid Fatahi Valilai (Discover Applied Sciences)
Abstract Product demand prediction is highly important as levels of inventory, customers forecast accuracy and overall performance are directly impacted by this demand planning. As the main problem of this research, accurate forecasting as a crucial challenge for achieving high performance is targeted. This paper has developed a demand planning framework with analytical capabilities of sales and consumer patterns, historical sales, and seasonality data to maximize the company’s ability to satisfy consumer demand. The framework has been implemented in an empirical business environment and has been analyzed from a practical viewpoint. A comprehensive picture of all factors is acquired from this viewpoint for successful implementation. The primary objective of the framework is to enhance the demand planning process in joint forecast project and how these improvements will help other business units, a crucial component of the supply chain, to achieve greater performance levels. As a result, the process of demand planning is examined from a system viewpoint for its integration with the supply chain E2E process, performance, forecasting methods, and logistical structure which serve as the foundation for assessment of the current condition and context of the new system. A deeper focus is placed on the analysis of the demand planning processes and forecasting techniques. Several root causes are found based on the customer forecast inputs like forecast horizon, forecasting methods, standard process with customers, performance measurement and communication with customers. Integration of JDA, ERP, and other data sources, combined with flexible forecasting tools, greatly refines the demand planning while enhancing overall decision making. By blending statistical models with real-time customer insights, the firms maintain an agile, efficient supply chain that can quickly adapt to market disruptions.